Pemanfaatan Tanah Aset Daerah Provinsi Sumatera Barat Melalui Perjanjian Bangun Guna Serah (Build Operate Transfer) - Jalmas, David; Warman, Kurnia; Rosari, Anton (Lareh Law Review, 2024)
To promote tourism in West Sumatra, particularly in the city of Bukittinggi, the provincial government of West Sumatra actively seeks investors to develop star-rated international hotels. Consequently, PT. Grahamas Citrawisata was appointed as the investor in this collaboration, which is formalized in Agreement No. 17.020/L/1990. However, during the implementation of this agreement, several issues have arisen, such as the perceived inadequacy of the compensation distribution from the BOT agreement compared to the reported revenues or balance sheets provided by Novotel Bukittinggi. The research problem formulation for this study includes: 1) The utilization of provincial asset land in West Sumatra for the construction of the Triple Tree Bukittinggi Hotel & Resort using the build operate transfer model and the agreement drafting process. 2) The implementation of the build operate transfer (BOT) agreement in utilizing provincial assets for the construction of the Triple Tree Bukittinggi Hotel & Resort. 3) The status of the land and building of the Triple Tree Bukittinggi Hotel & Resort after the expiration of the build operate transfer agreement. This research is an empirical juridical legal study, employing data collection techniques such as interviews and document studies. Based on the research findings, it is concluded that the utilization of the government asset land uses the build operate transfer method due to limited funds, experience, and skills necessary for the hotel development and management. The build operate transfer (BOT) agreement is documented in Agreement No. 17.020/L/1990, agreed upon by both parties on August 27, 1990. The implementation of the agreement occurs in three stages: 1) Construction (Build), 2) Utilization or Management (Operate), 3) Handover (Transfer). Additionally, the research examines the status of the land and building after the BOT agreement ends and the steps taken by the provincial government in managing the hotel post-BOT agreement.. Keywords: Build Operate Transfer Agreement , Land, Regional Assets, Regional Property